( x + 2xy ) * ( 2x - 1 )
x-y x^2-2xy+y^2 x+y
(x^3-2x^2y+y^2x+2x^2y-2xy^2)* ( 2x - 1 )
(x-y) (x^2-2xy+y^2 ) x+y
(x^3-2x^2y+y^2x+2x^2y-2xy^2) *(2x - 1 )
(x-y) (x^2-2xy+y^2 )( x+y)
(x^3-xy^2) *(2x - 1 )
(x-y) (x^2-2xy+y^2 )( x+y)
x(x^2-y^2)*(2x - 1 )
(x-y) (x^2-2xy+y^2 )( x+y)
x((x-y)(x+y)))*(2x - 1 )
(x-y) (x^2-2xy+y^2 )( x+y)
x*(2x - 1 )
(x^2-2xy+y^2 )
x*(2x - 1 )
(x-y)^2
подставляем
-2(-4-1) = 10
9 9
Sn = (a₁(q^n - 1)) / (q - 1).
Отсюда a₁ = Sn* (q - 1)) / (q^n - 1) = 5,5*(-2-1) / (-32-1) =
= -16,5 / -33 = 1/2.
Пятый член этой прогрессии а₅ = а₁*q^(n-1) = 1/2 * (-2)⁴ = 1/2*16 = 8.